Uso da eletrocoagulação no interior do reator anaeróbio híbrido (EC-UAHB) para a remoção de fosfato - Manzoni Junior, Milton (2024)
The presence of nutrients, such as phosphate, in wastewater, originating from both domestic and industrial sources, can result in eutrophication when discharged into water bodies, causing harmful environmental imbalance to local fauna and flora. Although domestic sewage treatment methods using anaerobic biological processes, such as Upflow Anaerobic Hybrid Reactors (UAHB), are effective in reducing organic matter, they tend to be inefficient in phosphate removal. In this context, electrocoagulation (EC) emerges as a viable alternative to enhance efficiency in removing both organic matter and phosphate, showing promise for combination with UAHB reactors. This study aimed to evaluate the effectiveness of iron electrode electrocoagulation in a UAHB reactor, with electric current density and electrolysis time as independent variables and phosphate removal as the response variable. For electrochemical treatment operation, electrodes were arranged in a monopolar parallel configuration, alternating polarity every 15 minutes to prevent passivation layer formation. Preliminary tests assessed EC efficacy in phosphate reduction, monitoring results hourly for 24 hours post-electrolysis, using an electric current density of 1.78 mA cm-2 and electrolysis times of 15, 30, 45, and 60 minutes. Based on these analyses, an 8-hour periodicity was established for EC application. In Stage 1, a Rotatable Central Composite Design was employed to define 10 trials with different combinations of electric current density and electrolysis time, maintaining an 8-hour hydraulic retention time (HRT). Statistical analysis determined the optimal operating point (3.4 mA cm^-2 and 54 minutes), with a statistical prediction of 41% phosphate removal. Stage 2 validated this prediction by applying optimal conditions, achieving 43% phosphate removal. In Stage 3, the optimal point was maintained with a 6-hour HRT, resulting in 82% soluble chemical oxygen demand (COD) and 98% soluble phosphate removals. Stage 4 applied the optimal conditions with a 4-hour HRT, resulting in 82% soluble COD and 86% soluble phosphate removals. Zeta potential analyses in the last three stages verified effluent coagulation conditions by EC. Furthermore, microbiota evaluation in biofilms adhered to electrodes identified species such as Anaerolineaceae bacterium (Stage 2) and Acetoanaerobium noterae (Stages 3 and 4). The highest phosphate removal was achieved operating the EC-UAHB reactor with a 6-hour HRT using the determined optimal point. Thus, effective phosphate removal was only achieved by applying electrochemical treatment in the UAHB reactor.